2017
DOI: 10.3390/nano7100319
|View full text |Cite
|
Sign up to set email alerts
|

Feedback System Control Optimized Electrospinning for Fabrication of an Excellent Superhydrophobic Surface

Abstract: Superhydrophobic surface, as a promising micro/nano material, has tremendous applications in biological and artificial investigations. The electrohydrodynamics (EHD) technique is a versatile and effective method for fabricating micro- to nanoscale fibers and particles from a variety of materials. A combination of critical parameters, such as mass fraction, ratio of N, N-Dimethylformamide (DMF) to Tetrahydrofuran (THF), inner diameter of needle, feed rate, receiving distance, applied voltage as well as temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Metal corrosion is caused by the direct contact between metal and water, oxygen, or acid solution, so the effective method of metal corrosion prevention is to isolate the metal itself from contacting with water, oxygen, or acid solution [ 170 , 171 ]. Usually, an anti-corrosion coating with a superhydrophobic surface could effectively reduce the contact range between the metal matrix and corrosion solution [ 172 ]. Therefore, some self-healing material due to its specific property could be applied as an anti-corrosion material, which not only has good anti-corrosion effect but also has significantly enhanced durability [ 173 ].…”
Section: Application Of Transparent Electrospun Fibrous Membranementioning
confidence: 99%
“…Metal corrosion is caused by the direct contact between metal and water, oxygen, or acid solution, so the effective method of metal corrosion prevention is to isolate the metal itself from contacting with water, oxygen, or acid solution [ 170 , 171 ]. Usually, an anti-corrosion coating with a superhydrophobic surface could effectively reduce the contact range between the metal matrix and corrosion solution [ 172 ]. Therefore, some self-healing material due to its specific property could be applied as an anti-corrosion material, which not only has good anti-corrosion effect but also has significantly enhanced durability [ 173 ].…”
Section: Application Of Transparent Electrospun Fibrous Membranementioning
confidence: 99%
“…For these reasons, the optimization of drug combination has attracted considerable attention in recent years, and several methods for predicting the optimal combinatory drug concentrations have been proposed [13][14][15][16][17][18][19][20]. A feedback system control (FSC) method was developed to search for optimal synergistic combinatory drugs for the treatment of diseases [16].…”
Section: Introductionmentioning
confidence: 99%
“…The roughness can be fabricated by direct electrospinning of hydrophobic materials. Feedback system control scheme was applied for rapid identification of the optimal electrospun parameters to prepare superhydrophobic polystyrene membrane by one step electrospinning by Yang et al . Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…The roughness can be fabricated by direct electrospinning of hydrophobic materials. Feedback system control scheme was applied for rapid identification of the optimal electrospun parameters to prepare superhydrophobic polystyrene membrane by one step electrospinning by Yang et al 11 Chen et al reported that the electrospun polystyrene fibers with a high fraction of open holes were fabricated due to nonsolvent-induced phase-separation, which led to a superhydrophobic surface, and controlling the fraction of good solvent and nonsolvent can change the fiber morphology. 12 Spinning solution can mix polymers with hydrophobic nanoparticles to fabricate the roughness surface.…”
Section: Introductionmentioning
confidence: 99%